Reassessment of the TM 1517 odonto‐postcranial assemblage from Kromdraai B, South Africa, and the maturational pattern of Paranthropus robustus - (:unkn) unknown (My University, 2020)
Objectives: The Pleistocene taxon Paranthropus robustus was established in 1938 following the discovery at Kromdraai B, South Africa, of the partial cranium TM 1517a and associated mandible TM 1517b. Shortly thereafter, a distal humerus (TM 1517g), a proximal ulna (TM 1517e), and a distal hallucial phalanx (TM 1517k) were collected nearby at the site, and were considered to be associated with the holotype. TM 1517a-b represents an immature individual; however, no analysis of the potentially associated postcranial elements has investigated the presence of any endostructural remnant of recent epiphyseal closure. This study aims at tentatively detecting such traces in the three postcranial specimens from Kromdraai B.Materials and Methods: By using μXCT techniques, we assessed the developmental stage of the TM 1517b's C-M3 roots and investigated the inner structure of TM 1517g, TM 1517e, and TM 1517k.Results: The M2 shows incompletely closed root apices and the M3 a half-completed root formation stage. The distal humerus was likely completely fused, while the proximal ulna and the distal hallucial phalanx preserve endosteal traces of the diaphyseo‐epiphyseal fusion process.Discussion: In the hominin fossil record, there are few unambiguously associated craniodental and postcranial remains sampling immature individuals, an essential condition for assessing the taxon‐specific maturational patterns. Our findings corroborate the original association of the craniodental and postcranial remains representing the P. robustus type specimen. As with other Plio‐Pleistocene hominins, the odonto‐postcranial maturational pattern of TM 1517 more closely fits an African great ape rather than the extant human pattern.
Keywords: African Research